MENINGKATKAN LITERASI NUMERISI PADA ANAK USIA 5-6 TAHUN MELALUI PERMAINAN EDUKATIF PUZZLE ANGKA DI TK ABATA TAHUN AJARAN 2024/2025 - Afifah; Ananti Firdiana Sutopo; Nurul Umrotullatifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve numeracy literacy skills in children aged 5-6 years through educational media using number puzzles at TK ABATA Pagedangan, Tangerang Regency. The research employed the Classroom Action Research (CAR) method, conducted in two cycles. Cycle I was carried out from November 11-15, 2024, and Cycle II from November 18-22, 2024. The research subjects were 16 children in Group B, consisting of 9 boys and 7 girls. Each cycle involved planning, action implementation, observation, and reflection stages. The results indicated a significant improvement in children’s numeracy skills. In Cycle I, 31.25% of the children developed as expected, and 12.50% developed very well, totaling 43.75% who showed progress. In Cycle II, the percentage of children developing as expected increased to 12.50%, while those developing very well reached 87.50%, resulting in all children 100%, showing optimal progress. These findings demonstrate that using number puzzle games as an interactive learning method effectively enhances children’s numeracy literacy. This study recommends integrating educational games into learning activities to foster interest and improve numeracy skills in early childhood.